1983
DOI: 10.1007/bf01249128
|View full text |Cite
|
Sign up to set email alerts
|

Deficient natural killer cell (NK) activity and macrophage functioning in schizophrenic patients

Abstract: The cytotoxic potential of mononuclear blood cells from 27 chronic schizophrenic patients was evaluated using quantitative measures of natural killer cell activity and macrophage inhibition of tumor cell growth. 44% of the patients had some evidence of deficient in vitro mononuclear cell function which was not correlated with a qualitative or quantitative alteration in the histologic appearance of these peripheral blood cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…A reduction in NK cell activity was shown in teenage and adult autism patients, with 12 out of 31 patients showing lower activity in PBMCs via K562 chromium-release assays (Warren et al, 1987). Autistic patients showed no decrease in overall NK count, a similar result to schizophrenia (DeLisi et al, 1983), suggesting that it is the cells themselves that are dysfunctional.…”
Section: Immune Dysregulationmentioning
confidence: 97%
“…A reduction in NK cell activity was shown in teenage and adult autism patients, with 12 out of 31 patients showing lower activity in PBMCs via K562 chromium-release assays (Warren et al, 1987). Autistic patients showed no decrease in overall NK count, a similar result to schizophrenia (DeLisi et al, 1983), suggesting that it is the cells themselves that are dysfunctional.…”
Section: Immune Dysregulationmentioning
confidence: 97%
“…The activity of NK cells in schizophrenics has been found either to be decreased [18,54,55], unchanged [33,56,57 on admission], or increased [57] after several weeks of neuroleptic medication.…”
Section: Discussionmentioning
confidence: 99%
“…Even though limited information is available on which molecules have been changed in the pathophysiological changes in beige-J mice, these mice show defects in lysosome-containing cells, neutral protease activity in polymorphonuclear leukocytes, and other immunological functions, especially natural killer (NK) cell functions (7 -9). A large and growing body of evidence supports the notion that immune dysfunction may play a role in schizophrenia, whereas the involvement of NK cell activities in schizophrenic patients is still controversial (10). Our preliminary study showed that beige-J mice exhibited increased locomotor activity.…”
Section: Short Communicationmentioning
confidence: 57%
“…Interestingly, immunological dysfunction has been described as an etiology of schizophrenia (16). For example, NK cell activities were shown to be potently reduced in schizophrenic patients (10). It is unclear whether the augmentation of DA turnover in the limbic forebrain is due to immune dysfunction in beige-J mice.…”
Section: Short Communicationmentioning
confidence: 99%